Optimalisasi Strategi Promosi Digital di Era Digitalisasi: Sebuah Kajian Komprehensif pada PT Glamourix AFA Indonesia Skincare 2022-2023 - Hermanses, Bintang; Roswinanto, Widyarso (Journal of Emerging Business Management and Entrepreneurship Studies, 2023)
In the digitalization era, digital promotions are crucial for companies, including the skincare industry, such as designing digital promotion programs at PT. Glamourix AFA Indonesia Skincare 2022-2023. The method used in this research is descriptive-qualitative and field research by conducting literature studies, interviews, and observations. The research results show that PT. Glamourix AFA Indonesia needs to develop a digital promotional program design to achieve product sales targets. Promotion of skincare products is carried out by creating blog content, videos, and social media activities by providing special discounts—a digital promotion process for Emre PT products. GAI carries out four types of promotions: advertising on social media and Instagram, public relations by utilizing content via Instagram, direct marketing via instant messages on WhatsApp, and sales promotions by creating discount programs. Emre's digital promotion strategy for the 2022-2023 period that Emre can carry out is digital advertising by working with digital TV stations to market products by developing a digital promotional program design for PT. Glamourix AFA Indonesia Skincare is expected to be able to increase sales to a broader target consumer and be able to compete with competing companies in the increasingly tight skincare industry in Indonesia.